Endoscopic Resection and Mucosal Reconstitution With Epidermal Grafting: A Pilot Study in Idiopathic Subglottic Stenosis. (May 2022) - Davis, Ruth J.; Lina, Ioan; Motz, Kevin; Gelbard, Alexander; Lorenz, Robert R.; Sandhu, Guri S.; Hillel, Alexander T.
Objective: To describe technical aspects and surgical outcomes of endoscopic resection and mucosal reconstitution with epidermal grafting (ie, the Maddern procedure) in the treatment of idiopathic subglottic stenosis. Study Design: Medical record abstraction. Setting: Johns Hopkins Hospital. Methods: Retrospective series of 9 adults with idiopathic subglottic stenosis who underwent the Maddern procedure by a single surgeon over a 5-year period. Prespecified outcomes included (1) perioperative outcomes (Clavien-Dindo grade 4/5 complications, need for staged tracheostomy, hospital length of stay), (2) postoperative outcomes (peak expiratory flow rate [PEFR], need for subsequent airway surgery, tracheostomy at follow-up), and (3) patient-reported quality-of-life outcomes (Clinical COPD Questionnaire, Voice Handicap Index–10, Eating Assessment Tool–10, and 12-Item Short Form Version 2). Wilcoxon matched-pairs signed rank test and Kaplan-Meier analysis were performed. Results: There were no Clavien-Dindo grade 4/5 complications; 2 patients required unplanned staged tracheostomy; and the median length of stay was 3 days. Following endoscopic resection and stent removal, a median of 2 laser resurfacing procedures were required. Two patients developed recurrent stenosis requiring cricotracheal resection (CTR). There were significant improvements in PEFR, Clinical COPD Questionnaire, and Voice Handicap Index–10, without significant difference in Eating Assessment Tool–10. The 12-Item Short Form Version 2 approximated the population norm. Kaplan-Meier analysis demonstrated significant improvement in time to surgery after the final laser resurfacing. Conclusion: The Maddern procedure has a low complication rate and offers durable physiologic improvement in PEFR, limiting need for additional procedures. Risks included need for CTR salvage, temporary tracheostomy, phlegm accumulation, and laryngospasm. It is a surgical option for patients with short dilation intervals who prefer to avoid the risks of CTR.